(untitled) (Current Horticulture, 2024)
A field experiment was conducted at the Regional Centre of ICAR-Central Tuber Crops Research Institute, Bhubaneswar, Odisha, India, during 2018-2020 on alfisols under rainfed conditions to identify most productive, resource use-efficient and remunerative taro-based cropping system. The experiment consisted of seven treatments, T1- sole taro, T2- sole maize, T3- sole pigeonpea, T4- taro+maize (5:1), T5- taro+maize (5:2), T6- taro+pigeonpea (5:1) and T7- taro+pigeonpea (5:2). The results revealed that the cormel equivalent yield (CEY) was greater in T1 and it was statistically on a par with T4 and T6. The LER of T4, T5, T6 and T7 were found >1. This indicated that all the above intercropping systems were biologically efficient. However, advantage of intercropping system was disappeared in T5, T6 and T7, when evaluated via ATER concept. The treatment T1 resulted in higher gross and net returns as well as B:C ratio however, it was statistically on a par with T4 and T6. Taro can be recommended for cultivation as a sole crop under upland ecosystem of eastern India. The treatment taro+maize (5:1) (T4) can also be recommended for cultivation under rainfed conditions of eastern India for efficient use of resources, and optimum yield and returns. The intercropping system taro+pigeonpea (5:1) (T6) can also be considered when more emphasis was given on soil health.